The Media Construction on Heretical Religious Teachings at Al-Zaytun Islamic Boarding Schools: A Study of the Media - Kurnia, Ulfa; Salbiah, Rahma (Universitas Islam Negeri Sunan Kalijaga, 2023)
This article aims to explore the issue of heretical deviations in the Al-Zaytun Islamic boarding school constructed by four online media sources: metro.suara.com, bandung.viva.co.id, rejabar.republik.co.id, and merdeka.com which had intensely reported on this controversy for weeks. It is intended to reveal what actually occurred in the institution and analyze how these media framed the issue critically. This study uses Norman Fairclough's Critical Discourse Analysis (CDA) model through three levels of analysis: critical language analysis, subjective interpretation of the discourse practices, and relevant information on the media's sociocultural practices. This research found that the media's claim that al-Zaytun Islamic boarding school engaged in radicalism is a construction of pseudo-reality. The text narrative is unclear, and the news facts are blurred, containing bias and prone to debates. The findings reveal that the actual reality constructed by the four online media is the contestation of elite groups over the discourse on heretical teachings against Al-Zaytun Islamic boarding schools.